Efficacy of dietary supplements as an adjunctive therapy for polycystic ovary syndrome: an umbrella meta-analysis - Wang, Rutong; Huang, Kongwei; Wang, Mengyao; Zou, Wenhui; Huang, Yujun; Jiang, Wei; Feng, Yingqi; Shen, Huilong; Lei, Xiaocan (Frontiers in Nutrition, 2025)
IntroductionPolycystic ovary syndrome (PCOS) affects 5–15% of reproductive-aged women and involves significant metabolic dysregulation, for which nutritional interventions show therapeutic potential. Methods: This umbrella meta-analysis synthesizes evidence from 46 randomized trials (n = 30,133) to evaluate dietary supplements targeting core PCOS pathways.MethodsThis umbrella meta-analysis synthesizes evidence from 46 randomized trials (n = 30,133) to evaluate dietary supplements targeting core PCOS pathways.ResultsKey nutraceuticals demonstrate clinically relevant benefits: myo-inositol significantly improves insulin sensitivity (HOMA-IR SMD = −0.81) and SHBG levels (SMD = 9.65) by enhancing glucose transporter activity; probiotics reduce systemic inflammation (CRP SMD = −0.82) via gut-microbiota modulation; omega-3 fatty acids ameliorate dyslipidemia (LDL-C SMD = −9.57; HDL-C SMD = 2.31) through anti-inflammatory mechanisms. Plant-derived compounds like curcumin lower fasting glucose (SMD = −3.43) via NF-ĸB pathway inhibition, while green tea catechins reduce adiposity. Significant heterogeneity arises from variations in supplement bioavailability, dosing protocols, and patient metabolic phenotypes. Nevertheless, consistent evidence confirms that targeted nutrient supplementation modulates insulin signaling, lipid metabolism, and hormonal balance in PCOS. Emerging research priorities include personalized nutrition protocols leveraging nutrigenomic interactions and antioxidant-rich formulations (e.g., vitamin E, selenium).DiscussionThis work establishes a mechanistic foundation for integrating evidence-based nutraceuticals—particularly myo-inositol, probiotics, and omega-3s—into PCOS management, offering clinically actionable strategies while highlighting needs for standardized dosing and bioavailability studies.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024602681.